2016
DOI: 10.1242/jcs.190702
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 modulates interferon-γ-stimulated signaling in brain microvascular endothelial cells

Abstract: Inflammatory response of blood-brain barrier (BBB) endothelial cells plays an important role in pathogenesis of many central nervous system inflammatory diseases, including multiple sclerosis; however, the molecular mechanism mediating BBB endothelial cell inflammatory response remains unclear. In this study, we first observed that knockdown of neuropilin-1 (NRP1), a co-receptor of several structurally diverse ligands, suppressed interferon-γ (IFNγ)-induced C-X-C motif chemokine 10 expression and activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 66 publications
3
35
0
Order By: Relevance
“…Meanwhile, IFN-γ could activate transcription factors STAT3, STAT5, and AP-1. The canonical and non-canonical signaling pathways form its complex signal network ( 106 128 ) (Figure 2 ).…”
Section: Ifn-γ In Osteoimmunologymentioning
confidence: 99%
“…Meanwhile, IFN-γ could activate transcription factors STAT3, STAT5, and AP-1. The canonical and non-canonical signaling pathways form its complex signal network ( 106 128 ) (Figure 2 ).…”
Section: Ifn-γ In Osteoimmunologymentioning
confidence: 99%
“…26 However, only 2 other reports studied the regulation of CXCL10 production by Rac1. On 1 hand, Wang et al 27 showed that knockdown of Neuropilin-1, a co-receptor of several structurally diverse ligands, suppressed CXCL10 expression in human brain microvascular endothelial cells in a Rac1-STAT1dependent manner. On the other hand, Pedersen et al 28 showed that loss of Rac1 in keratinocytes increased the expression of CXCL10.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen-inducible endothelial-specific NRP1 knockout mice were generated and administered tamoxifen (MilliporeSigma, Burlington, MA, USA) as previously described (12). Animal care and experimental procedures were performed under protocols approved by the Institutional Animal Care and Use Committees of Mayo Clinic.…”
Section: Micementioning
confidence: 99%